PERHITUNGAN PREMI DENGAN PENERAPAN DEDUCTIBLE PADA MODEL AKTUARIA UNTUK SICKNESS INSURANCE PERTANGGUNGAN SATU TAHUN - Norisca Lewaherilla; Gabriella Haumahu (VARIANCE: Journal of Statistics and Its Applications, 2019)
Health insurance is an insurance product that provides benefits if the insured is exposed to the risk of an accident or illness and causes loss of income, thus requiring costs. The most important benefit in this study from sickness insurance is the reimbursement of medical expenses. The design of determining premiums by applying deductibles (flat deductibles) is seen as one of the insurance policy policies that meet the principles of determining premiums. The actuarial aspects considered in the health insurance model in this study for the calculation of premiums relating to the type of insurance benefits with expense reimbursement for a period of one year coverage, with due regard to the type of work. The purpose of this study is to see the applied of deductible to the premiums that must be paid to insurance companies that provide benefits for claims submitted. The policy of applying deductibles certainly makes the amount of reimbursement change.